Anti-tumor effect and hepatotoxicity mechanisms of psoralen - Meng, Dandan; Dong, Yanling; Shang, Qingxin; Sun, Ziyuan (Frontiers in Pharmacology, 2024)
In recent years, natural products have gradually become an important source for new drug development due to their advantages of multi-components, multi-targets, and good safety profiles.Psoralen, a furanocoumarin compound extracted from the traditional Chinese medicine psoralea corylifolia, is widely distributed among various plants. It has attracted widespread attention in the research community due to its pharmacological activities, including antitumor, anti-inflammatory, antioxidant, and neuroprotective effects. Studies have shown that psoralen has broad spectrum anti-tumor activities, offering resistance to malignant tumors such as breast cancer, liver cancer, glioma, and osteosarcoma, making it a natural, novel potential antitumor drug. Psoralen mainly exerts its antitumor effects by inhibiting tumor cell proliferation, inducing apoptosis, inhibiting tumor cell migration, and reversing multidrug resistance, presenting a wide application prospect in the field of antitumor therapy. With the deepening research on psoralea corylifolia, its safety has attracted attention, and reports on the hepatotoxicity of psoralen have gradually increased.Therefore, this article reviews recent studies on the mechanism of antitumor effects of psoralen and focuses on the molecular mechanisms of its hepatotoxicity, providing insights for the clinical development of low-toxicity, high-efficiency antitumor drugs and the safety of clinical medication.